Our guest: Eka Kurniawan: “It would be great to live around people who read literature from across the world” - Agnès Bardon (The UNESCO Courier, 2022)
Since the publication of his first novel Beauty Is a Wound in 2002, Indonesian writer Eka Kurniawan has made himself a name internationally. Drawing on the myths and beliefs of his country while combining earthliness and poetry, magic and realism, his short stories have been translated into more than thirty languages.